ЗНАЧЕНИЕ КРИМИНАЛИСТИЧЕСКОЙ ХАРАКТЕРИСТИКИ ПРЕСТУПЛЕНИЙ В ПОЗНАВАТЕЛЬНОЙ ДЕЯТЕЛЬНОСТИ СЛЕДОВАТЕЛЯ ПРИ ОСМОТРЕ МЕСТА ПРОИСШЕСТВИЯ (Journal of actual problems of jurisprudence, 2019)
In clause the opportunities of use криминалистической of the characteristic of crimes for an establishment обстоятелбств of acrime are considered at survey of a place of incident.